The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/joc.3973
|View full text |Cite
|
Sign up to set email alerts
|

Iberian extreme precipitation 1855/1856: an analysis from early instrumental observations and documentary sources

Abstract: Flood events is the natural hazard that originated more damages and fatalities in the Iberian Peninsula in the last decades. While most 20th century extreme precipitation and flood episodes in Iberia have been documented, the same does not hold for most events that took place during the 19th century. This article describes the unusually high precipitation and associated impacts recorded during the 1855/1856 hydrological year. We combine newspaper reports, early instrumental precipitation series and sea level p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…3b, c, f, g). Supporting this result, previous studies have reported above average rainfall in Lisbon between 1864 and 1875, as well as unusually wet years in the Iberian Peninsula, such as 1856 (Kutiel and Trigo 2014;Domínguez-Castro et al 2015).…”
Section: General Overviewsupporting
confidence: 73%
“…3b, c, f, g). Supporting this result, previous studies have reported above average rainfall in Lisbon between 1864 and 1875, as well as unusually wet years in the Iberian Peninsula, such as 1856 (Kutiel and Trigo 2014;Domínguez-Castro et al 2015).…”
Section: General Overviewsupporting
confidence: 73%
“…This classification of atmospheric circulation into CWTs was first developed for the British Isles by Lamb (1972) and, later on, it was improved for an objective automated classification by Jenkinson and Collison (1977). This automated methodology was later applied for different areas in the Iberian Peninsula (e.g., Trigo and DaCamara, 2000;Paredes et al, 2006;Garcia-Herrera et al, 2007;Domínguez-Castro et al, 2014;Russo et al, 2014). In this work, prevailing CWTs at regional scale where determined using the simple Geostrophic approximation according to the methodology proposed by Trigo and DaCamara (2000).…”
Section: Circulation Weather Type Classificationmentioning
confidence: 99%
“…Within the Iberian Peninsula several studies have applied LWTs to precipitation (Cortesi et al, 2014(Cortesi et al, , 2013Domínguez-Castro et al, 2015;Paredes et al, 2006). For example, Cortesi et al 2014and Paredes et al (2006) clearly show that much of the rainfall falling into the Iberian peninsula is driven by few LWTs, with the westerly, south-westerly and cyclonic being the most predominant ones.…”
Section: Weather Patternsmentioning
confidence: 99%